Highly crystallized glass-ceramics from high content gold tailings via a one-step direct cooling method. Issue 22 (11th May 2022) - Jiang, Ke; Wu, Wei; Ren, Boyong; Li, Meng; He, Jiaxing; Xu, Enze; Liu, Junwu; Tong, Guoqing; Zhong, Honghai; Jiang, Yang
Abstract : Highly crystalline glass-ceramics were successfully manufactured via a one-step direct cooling method using Shuangqishan (Fujian, China) gold tailings as raw materials. Abstract : Highly crystalline glass-ceramics were successfully manufactured via a one-step direct cooling method using Shuangqishan (Fujian, China) gold tailings as raw materials. A series of glass-ceramics were prepared by controlling the gold tailings addition and post-treatment. X-ray diffraction results show that the crystalline phase of glass-ceramics samples with high tailing addition content (65–80 wt%) is akermanite phase (Ca2 MgSi2 O7 ). By contrast, the main phase of 60 wt% and 55 wt% tailings addition samples is diopside (CaMgSi2 O6 ) crystalline phase. In addition, although glass-ceramics have typical fracture characteristics of brittle materials, the crack propagation in the fracture process is disturbed by grains, resulting in the deviation of the fracture path in terms of macroscopic and microcosmic observation. Based on the investigation of samples with different tailings additions, glass-ceramics with 60 wt% tailings contents show excellent mechanical properties with a density of 2.89 g cm −3, a Vickers hardness value of 8.17 GPa, and a flexural strength of 116 MPa after 950 °C heat treatment. This study further confirms the possibility of using Shuangqi Mountain gold tailings as the raw materials for highly crystalline glass-ceramics, which shows great potential for application in mass production.